Exaptation and phonological change - Kaźmierski, Kamil (De Gruyter Mouton, 2015)
Looking at the fate of the concept of exaptation in historical linguistics, this article attempts an extension of exaptation from morphosyntactic change to phonological change. It argues that explicit recognition of the links between language change and other manifestations of Darwinian evolution can provide a context in which the use of this concept might be justified. First, an overview of the applications of exaptation in linguistics is provided (Section 2). Next, the historical data, that is the raisings of the close–mid long vowels as part of the Great Vowel Shift, as well as the lowerings of the short vowels as part of the Short Vowel Shift, adduced in this paper to verify the usefulness of exaptation in studying sound change are presented (Section 3). Consequently, two ways in which exaptation can be applied in the analysis of these data are presented: first (Section 4.1), a superficially evolutionary approach, which treats exaptation as a biologically inspired metaphorical label, and second (Section 4.2), a strictly evolutionary approach, which goes beyond metaphorical extensions of biological terms to linguistics, and which instead treats languages as truly evolutionary systems.
Keywords: exaptation; linguistic evolution; Great Vowel Shift; phonological change